Efektivitas Ekstrak Daun Kari (Murraya koenigii) Sebagai Larvasida Alami Terhadap Kematian Larva Nyamuk Culex Sp - Khairunnisa; zulfikar, zulfikar; Shafira, Mega; Aditama, Wiwit; Arianto, budi; sari, arnida (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
The Culex genus of mosquitoes makes up the majority of the mosquitoes in our area. The West Nile virus, filariasis, Japanese encephalitis, and St. Louis encephalitis are only a few of the illnesses spread by this mosquito. Culex quinquefasciatus, a mosquito in the genus Culex that is known to transmit the diseases chikungunya and filariasis, is a significant mosquito species. The study's objective was to ascertain whether Culex Sp mosquito larvae died after receiving doses of curry leaf extract (Murraya koenigii) of 2 ml/200 ml, 4 ml/200 ml, and 8 ml/200 ml. Three hundred Culex species larvae served as the study's subjects. The One Way ANOVA test was employed for data analysis. The outcomes shown that Culex sp. larval mortality in the treatment Curry leaf extract (Murraya koenigii) doses of 2 ml/200 ml of water were 16.7%, 4 ml/200 ml of water were 21.7%, and 8 ml/200 ml of water were 25%. One way ANOVA analysis yielded a p value of 0.003 (0.005), indicating that curry leaf extract (Murraya koenigii) is effective as a natural larvi The dose that is most successful, with a p value of 0.001, is 4 ml/200 ml of water. It is envisaged that the community will be able to employ and make use of curry leaf extract (Murraya koenigii) as a substitute for killing Culex sp. larvae.